Analysis Of Mathematical Reasoning Ability in Terms of Mathematical Self-Efficacy of MAN 2 Pekanbaru Students - Masrianti Fadillah; Maimunah, Maimunah; Hutapea, Nahor Murani (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The mathematical reasoning ability of each student is very important to be able to make them use reasoning in patterns and traits, and perform mathematical tricks to produce valid generalizations, proofs, and statements. The activity of generalizing, proving, and making valid statements requires self-confidence. Confidence is in the form of Self-Efficacy and becomes an internal factor related to mathematical reasoning abilities. describing mathematical reasoning abilities in terms of students' mathematical self-efficacy is the aim of this study using a descriptive qualitative approach. Data collection techniques were questionnaires to measure students' self-efficacy, written tests to measure students' mathematical reasoning abilities, and interviews. The research subjects were 30 students of class XII MAN 2 Pekanbaru. The results of the study found that: (1) 26.67% of students with high mathematical reasoning abilities were accompanied by high or moderate self-efficacy; (2) 56.67% of students with moderate mathematical reasoning abilities are accompanied by high, medium, or low self-efficacy; (3) 16.67% of students with low mathematical reasoning ability are accompanied by moderate or low self-efficacy; (4) 43.33% of students can perform calculations based on certain rules; (5) 76.67% of students can do direct proof; and (6) 75.83% of students can provide valid arguments. It can be concluded that the level of mathematical reasoning ability is not always on the same level as students' self-efficacy, but the best mathematical reasoning ability is always followed by good self-efficacy. So, students' self-efficacy needs to be increased to be able to apply better mathematical reasoning abilities.